거대억새 파티클보드로 제조된 세라믹의 특성 - 오승원; Seung Won Oh; 박희준; Hee Jun Park; 황정우; Jung Woo Hwang (목재공학, 2014)
거대억새의 활용방안을 찾기 위하여 거대억새 파티클로 보드를 제조한 후 수지함침율 50%일 때 탄화온도 600∼1,200°C별로, 탄화온도 800°C일 때 수지함침율 30∼60%별로 탄화하여 세라믹을 제조한 후 물성을 조사하였다. 탄화온도가 증가함에 따라 탄화 후 밀도, 두께감소율, 길이감소율 및 중량감소율도 증가하였다. 수지함침율이 증가함에 따라 탄화 후 밀도, 길이감소율 및 중량 감소율은 증가하였으나 두께감소율은 감소하였다. For new use development of miscanthus sinensis var. purpurascens, which investigated properties of ceramics made from different carbonization temperature (600∼1,200℃) and percentage of resin impregnation(30∼60%) using a mincanthus board. As the carbonization temperature increased, the density, thickness shrinkage, linear shrinkage, weight loss were increased. As the percentage of resin impregnation increased, the density, linear shrinkage and weight loss were increased. On the other hand, thickness shrinkage decreased.